Study of factors related to the reflection abilities of dental trainees. (7th September 2015) - Oto, T.; Obayashi, T.; Taguchi, N.; Ogawa, T.
Abstract: Introduction: This study analysed the internal and external factors related to the reflection abilities of dental trainees. Participants and methods: We created transcripts from oral presentations by the dental trainees of Hiroshima University Hospital ( n = 35, 2012–2013) at a significant event analysis conference. The reflection depths were compared between the trainees of the university hospital and external clinical combination groups. We determined and statistically analysed the reflection depths. Results: At the end of training, a Mann–Whitney U ‐test revealed a significant difference in the median reflection depths of the groups ( U = 66, W = 342 and P = 0.007). The results of multiple regression analysis indicated a significant relation between the reflection depth and external training completion ( P = 0.024). There were no relations with other factors, including gender and academic background. Conclusion: Experiences in external clinics create a close connection between the staff and trainees because communities of practice can cause deeper reflections. We need to create small groups in large‐scale organisations such as university hospitals. This construct can be adapted not only for Japanese dental trainees but also for global dental and other medical trainees.